Retracting the juristic opinion in the Maliki Mazhab: An inductive juristic study / Abderrahman Ethmane - Abderrahman , Ethmane (2018)
This research concerns a juristic topic, that is to say the jurist’s view and withdrawing his first saying. The research will rely on the opinions of Imam Malik and Ibn Al-Qasim because of their special position in the Maliki’s Madhab (the Maliki’s School of Thought). The researcher attempts to clarify the notion of retracting the juristic opinion, the legal validity of the retracted opinion, understanding the reasons lie behind retracting the juristic view, mentioning the juristic opinions that were retracted by the two Imams, and then mentioning what are accepted from those retracted opinions in the Madhab. The researcher is applying the inductive method in collecting the retracted opinions from the authoritative Maliki’s books. He will also apply the analytical method to know the reasons behind retraction of the two Imams and also to reach the accepted opinions in the Maliki’s Madhab from such views. The researcher will apply the comparative method in the first jurisprudence chapter to discuss the opinions of the Maliki’s jurisprudents. The study comes to the conclusion that saying of Ibn Al-Qasim or his narration in the Mudawwanah (refers to a especial book) is usually the accepted saying, dissimilarities of sayings and narrations from the two Imams do not mean that they retracted one of the two opinions. The retracted juristic opinion is not nullified, the retracted juristic opinion does not attribute to the jurist who retracted it as saying but it can be considered his Madhab provided that it was in accordance with his source and principle, but it cannot be ascribed to him unless his retraction of such view is mentioned. The reasons for retracting opinions for the tow Imams can be traced back to five things: (1) the conflict of verbal or practical legal evidence, (2) applying jurisprudential evidence such as the interest and blocking pretense, (3) applying the Fiqh maxim such as considering intention and speech in the oath, (4) taking precaution and (5) discovering legal text for Mujtahid or the opinion Mujtahid for follower such as the opinion of Malik in the case of Ibn al-Qasim. The two Imams retracted 173 issues, 126 for Malik and 47 for Ibn Al-Qasim. The researcher recommends collecting cases of retraction of other jurists of the Madhab such as Sahnun as the researcher observed that Sahnun retracted may of his sayings. The researcher also recommends to benefit from the retracted opinions in dealing with the new issues as all Fiqh opinions can be used for analog or interpretation. Moreover, the researcher recommends the contemporary jurists to revise their independent judgment (Ijtihad) and their legal ruling (Fatwa). He also recommends to study the relationship between the retracted opinions and other schools of thought to measure the remoteness and closeness of the first and the last opinions.